Detecting the influence of additives on asphalt concrete durability - Sarsam, Saad Issa; Mashaan, Nuha (Penerbit Universiti Kebangsaan Malaysia, 2022)
Modification of asphalt cement with additives is a sustainable issue. An attempt was made in the present assessment to detect the influence of modification of the asphalt binder by 2 % silica fumes and 4 % fly ash additives on the durability in terms of fatigue life of asphalt concrete mixture under short-term and long-term ageing processes and moisture damage. Asphalt concrete slab samples of wearing course was prepared and compacted by roller. The beam specimens of 400 mm length and 50 mm height and 63 mm width were extracted from the slab samples. The beam specimens had practiced the four-point repeated flexural bending beam test. The fatigue life was monitored as the number of load repetitions to reach the failure under three constant micro strain levels of (250, 400, and 750). The reduction in fatigue life after long-term ageing for control, silica fumes modified, and fly ash modified mixtures was (74.7, 38.4, and 60) %, (66.2, 52.4, and 64.3) %, (63.9, 63.1, and 57.5) % under 250, 400, and 750 microstrain levels respectively. However, the reduction in fatigue life after practicing moisture damage for control, silica fumes modified, and fly ash modified mixtures was (71.2, 59.6, and 37.2) %, (37.1, 64.9, and 11.2) %, (71, 84.8, and 32.2) % under (250, 400, and 750) microstrain levels respectively. It was concluded that Fly ash exhibit lower susceptibility to long-term ageing process as compared to other mixtures, while silica fumes exhibit lower susceptibility to moisture damage as compared to other mixtures.